The Urgency of Digital Villages in Overcoming Blank Spots in the 3T Area - Muhtar, Muhtar; Wuryanta, AG Wenats; Wahyono, Dwi; Sugiarto, Agus; Anungrah, Annisa Putri (Universitas Pahlawan Tuanku Tambusai, 2024)
Taar Village is one of the villages in South Dullah District, Tual City, Maluku. Geographically, Dessa Taar is located in South Dullah District, Tual City, a distance of 2 km from the center of Tual City, Maluku. The uniqueness of Taar Village is that it is famous for a traditional ritual event called the Opening Sasi Hoat or Teluk UN Tradition, the view of Tavidu Bay Beach and is also famous for the taste of Baronang fish (the local name for Samandar Fish) and the Nudibranch species. Taar Maluku Village can be reached in approximately 5 minutes using land transportation and excellent two-lane highway access. When discussing with the Village Head and Taar Maluku Village officials, they encountered a number of problems regarding the blank spot area problem faced by the people of Taar Maluku Village as well as being the reason why it was still a little difficult for the community to get the signals used for communication. The problem in question is the lack of information and education regarding the Urgency of Digital Villages in Overcoming Blank Spots in the 3T Era. Areas that are still experiencing Blank Spot Areas, especially in Taar Village, South Dullah District, Tual City, Maluku. To overcome this problem, an alternative solution that can be implemented is the author discussing with village officials and suggesting the use of Village Digitalization to be able to overcome the Blank Spot Area in Taar Village, South Dullah District, Tual City, Maluku, so that Taar Village can become a Digital Village and get a signal to communicate as well as in big cities. Therefore, the aim of this community service is to see the potential of digitalizing villages to become digital villages in improving community welfare in Taar Village, South Dullah District, Tual City, Maluku. To obtain the data used were observation and literature study. This service activity is an educational effort to increase the digitalization of Digital Villages which can improve the welfare of the community in Taar Village, South Dullah District, Tual City, Maluku. As a manifestation of the author's thoughts, there are several efforts and breakthroughs offered, namely providing education on the use of Digital Village Digitization to overcome Blank Spot Areas in the 3T area in Taar Village, South Dullah District, Tual City, Maluku so that it can help overcome Blank Spot Areas and become a solution for village communities. Taar has his right as a citizen to get a good signal when communicating in Taar Village, South Dullah District, Tual City, Maluku.